Knowledge hiding through the lens of abusive supervision, moral disengagement and self-efficacy - Hina Samdani; Nida Kamal; Zahra Saleem (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2023)
In today's dynamic world, knowledge economy has become a driving factor for national socio-economic growth and overall development. The lynchpin of knowledge economy and ultimately that of national economy is creativity which has to be seen and realized through the prism of collaborative instead of standalone wisdom. This study focuses on identifying such factors that lead to knowledge hiding, and interpersonal factors that hinder knowledge hiding by facilitating knowledge sharing. The study analyses a mediatedmoderated model by taking the mediation effect of moral disengagement between abusive supervision and knowledge hiding and analyzing knowledge self-efficacy as a moderator between moral disengagement and knowledge hiding. This has been achieved by grounding on social learning theory, social cognitive theory, and self-efficacy theory and targeting full-time faculty members working in HEIs of the public and private sector of Pakistan. By collecting data from 500 faculty members through proportionate random sampling, the analysis of the study has been carried out through empirically testing the hypothesis employing CFA and SEM, using AMOS software. The analysis revealed that Abusive supervision enhances evasive knowledge hiding, such that abusive supervision increases the moral disengagement of faculty in the HEIs and in turn increase the knowledge hiding behavior carried out by faculty. The moderation results revealed that knowledge self-efficacy is not able to reduce the impact of moral disengagement on knowledge hiding among faculty members in the Pakistani HEIs.
Keywords: 330; Abusive supervision; moral disengagement; knowledge self-efficacy; tacitevasive knowledge hiding; higher education institutions (HEIs)